2021
DOI: 10.1039/d1cc02956h
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Mproinhibition by a zinc ion: structural features and hints for drug design

Abstract: Structural data on SARS-CoV-2 main protease in complex with a zinc-containing organic inhibitor gave hints on the presence of a zinc binding site involving the catalytic relevant cysteine and histidine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…A computational study has confirmed possible inhibition of RdRp and M Pro by zinc ions 21 , 22 . Additionally, the crystal structure of SARS-CoV-2 M Pro has confirmed the interactions of Zn 2+ in the active site 23 , 24 . Although the structural studies clearly confirmed that a zinc ion inhibits SARS-CoV-2 M Pro by binding to the active site, it was also found that the experimentally determined affinity between the protein and the metal ion does not appear to be high enough for any real therapeutic applications of zinc supplementation, at least in its ionic form 23 .…”
Section: Introductionmentioning
confidence: 70%
“…A computational study has confirmed possible inhibition of RdRp and M Pro by zinc ions 21 , 22 . Additionally, the crystal structure of SARS-CoV-2 M Pro has confirmed the interactions of Zn 2+ in the active site 23 , 24 . Although the structural studies clearly confirmed that a zinc ion inhibits SARS-CoV-2 M Pro by binding to the active site, it was also found that the experimentally determined affinity between the protein and the metal ion does not appear to be high enough for any real therapeutic applications of zinc supplementation, at least in its ionic form 23 .…”
Section: Introductionmentioning
confidence: 70%
“…3B). 66,88 Although zinc salts can inhibit SARS-CoV-2 M pro , they exhibit nearly no activity against SARS-CoV-2 in infected Vero E6 cells. Zinc salts along with an ionophore, Quercetin, could inhibit SARS-CoV-2 viral loads by two-fold 66 , suggesting that appropriate complexes may achieve a better clinical outcome in the fight against COVID-19.…”
Section: Metal Chelation Based Antiviral Strategymentioning
confidence: 99%
“…It was demonstrated that Zn ions are able to bind the catalytic dyad of SARS-CoV-2 main protease (Mpro) via metal coordination bonds with His41 and Cys145 residues [ 118 ]. However, when studied by Grifagni et al [ 119 ] using X-ray crystallography, the high affinity of the protein for Zn ions appeared to be insufficient to produce its inactivation. Tao et al demonstrated the ability of Zn gluconate (a common zinc supplement) to inhibit the proteolytic activity of PLpro and Mpro [ 120 ].…”
Section: Nanomaterials For Covid-19 Prevention and Treatmentmentioning
confidence: 99%